(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The La Niña phenomenon often causes significant changes in sea surface temperature and deep-sea ecosystem dynamics in the context of global climate change. This study focuses on the impact of the 2020–2022 Triple-Dip La Niña in the Lombok Strait, which potentially affects maritime biological equilibrium. The research aims to identify and understand the variability of Sea Surface Temperature (SST) and chlorophyll-a concentrations during the Triple-Dip La Niña period. The study utilizes Sea Surface Temperature (SST) and chlorophyll (chlor_a) data from the Aqua-MODIS satellite, as well as wind direction and speed data in the form of Windrose diagrams in Mataram, West Nusa Tenggara, from 2020 to 2022, with a three-month interval to examine the variability in SST and chlorophyll-a concentrations. Statistical approaches, including correlation coefficient calculations, were applied to determine the relationships between variables. It was found that the highest temperature occurred in 2020, while the highest chlorophyll-a concentration was also recorded in the same year, particularly in coastal areas where the sea surface temperature was relatively lower than the surrounding areas. The results indicate a weak correlation between chlorophyll-A and SST in the Lombok Strait region.